Britain, Turkey and the Soviet Union, 1940–45 - Tamkin, N. author. aut Link
XI, 267 p.
Keywords: This book draws on the latest archival releases – including those from the secret world of British intelligence – to offer the first comprehensive analysis of Anglo-Turkish relations during the Second World War, with a particular emphasis on Turkey's place in the changing relationship between Britain and the Soviet Union.